Root microbiota alters response to root rot in Rhododendron delavayi Franch - Tang, Jing; Xiao, Yufeng; Xu, Xiaorong; Tang, Ming; Zhang, Ximin; Yi, Yin (Frontiers in Microbiology, 2023)
Root microbiota have a significant effect on plant health. However, the role of root microbiota in the resistance of Rhododendron against root rot is not known. In this study, we employed amplicon 16S and ITS sequencing to investigate the bacterial and fungal communities associated with four distinct niches (bulk soil, rhizosphere, rhizoplane, and endosphere) of both healthy and diseased Rhododendron plants in the Baili Rhododendron nature reserve in China. The amplicon data analysis identified 182 bacterial genera and 141 fungal genera that were impacted by root rot across all niches. Specifically, the rhizoplane appeared to exert a selective gating effect, resulting in a reduction in the complexity of bacterial communities, but not fungal communities, in wild Rhododendron delavayi Franch roots. Nevertheless, the stress induced by root rot led to alterations in the root microbiota and compromised the gating function of the rhizoplane, thereby significantly increasing the complexity of the bacterial community within the plant root. In the root tissue following root rot outbreak, the relative abundance of the pathogenic species Pezicula brunnea and Diaporthe helianthi was enriched by as much as 6.13% and 1.71%, respectively. These findings provide novel insights into the contribution of enrichment of root-associated microbiota to wild plant hosts under the disease stress of root rot. The root rot-causing pathogenic fungi may interact with beneficial bacteria and induce plants to send out “cry for help” signals, which may encourage the specific assembly of microbiota. In the Rhododendron delavayi Franch root microbiota, we found 23 potentially beneficial microbes. Notably, certain beneficial bacteria, such as Sporolactobacillus and Stenotrophomonas, were found to accumulate in the rhizoplane and endosphere under root rot disease stress. Overall, our results lend support to our hypothesis that Rhododendron recruits protective microbes as a strategy to suppress root rot outbreaks. Future endeavors in isolating beneficial microbes capable of mitigating root rot have the potential to enhance plant resilience against root diseases.